(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: Changes in lifestyle and consumption patterns of Indonesian adolescents in recent years have shown an increasing trend towards a diet high in calories, fat, sugar, and salt and low in fiber. This condition has led to an increase in the rate of adolescent obesity, which is a major risk factor for degenerative diseases in adulthood. Based on the 2023 Riskesdas, the prevalence of adolescent obesity in Indonesia reached 18.7%, up from 13.5% in 2018. One of the effective promotive-preventive efforts is through balanced nutrition education in the school environment. Objective: This activity aims to improve the knowledge, attitudes, and behavior of adolescents about the principles of balanced nutrition and encourage the implementation of healthy eating patterns to prevent obesity and degenerative diseases. Methods: The activity was carried out through the stages of preparing educational materials, implementing interactive education, demonstrating the contents of my plate, and evaluating using pre-test and post-test. Results: The balanced nutrition education activity held at SMP Swasta 102114244 Nusantara Lubuk Pakam successfully attracted the attention and interest of all students. The participants’ enthusiasm was evident from the start of the activity, from the presentation of the material, the question and answer session, to the simulation of preparing a balanced nutrition menu based on the “Isi Piringku” guidelines. This is shown by the results of an increase in knowledge of 41.12% with a p value of <0.001. Conclusion: Balanced nutrition education is proven to be effective in increasing knowledge and forming healthy eating habits in adolescents. This program should be implemented sustainably in schools to prevent obesity and degenerative diseases